Measurement invariance of the strength of motivation for medical school: a multi-group confirmatory factor analysis - M. An; R. A. Kusurkar; L. Li; Y. Xiao; C. Zheng; J. Hu; M. Chen (BMC Medical Education, 2017)
Abstract Background The Strength of Motivation for Medical School-Revised (SMMS-R) questionnaire measures students’ motivation for studying medicine. It includes three subscales: ‘willingness to sacrifice’, ‘readiness to start’, and ‘persistence’. Measurement invariance is a prerequisite for group comparisons. The objectives of this study were to verify the factorial structure of the SMMS-R questionnaire and to investigate it’s measurement invariance. Methods A total of 989 medical students were approached, 930 cases were kept for data analysis. Factorial structure of and measurement invariance of the SMMS-R were tested using single and multiple group confirmatory factor analyses with Mplus. Trational Cronbach’s α along with McDonald’s ω and glb were used to measure internal consistency for each subscale. Results Internal consistency for subscales and the full instrument were within the acceptable range. A 3-factor structure of the Chinese version of the SMMS-R was supported. Full configural, metric and partial scalar invariance were obtained. Conclusions The SMMS-R showed measurement invariance across gender and two independent samples. So it can be used for group and cross-cultural comparisons.